FRI0564 Serum Uric Acid Testing Practices over Five Years among Incident Gout Cases. (15th July 2016) - Benis, A.; Jaffe, D.; Flores, N.; Gabay, H.; Morlock, R.; Klein, A.; Teltsch, D.; Chapnick, J.; Feldman, B.; Leventer-Roberts, M.
Abstract : Background: Gout is a chronic inflammatory disorder associated with elevated levels of serum uric acid (sUA), resulting in urate crystal deposits in soft tissues. Uncontrolled gout can lead to bone erosion and joint destruction, kidney stones, and uric acid nephropathy. Gout is treatable with medication and lifestyle change. Long-term sUA monitoring is needed to confirm that patients are achieving target levels (≤6 mg/dL, or <5 mg/dL in more severe cases). 1–3 Objectives: To describe incident gout cases and characterize these patients by subsequent sUA testing practices during 5 consecutive years. Methods: Data from Clalit Health Services were used to identify incident cases of gout (1/1/2003–31/12/2009) among members ≥25 years old with continuous enrollment in Clalit for 1 year prior to and 5 years subsequent to diagnosis (index date). Cases were identified based on the following criteria: a) 1 diagnosis of gout from a hospital or specialist visit; or b) ≥2 diagnoses of gout from a general practitioner (GP) visit and either elevated sUA (>6 mg/dL) or a purchase of colchicine or allopurinol. Cases were excluded if a member was concurrently diagnosed with a disease known to affect sUA (eg, renal insufficiency, cancer, Familial Mediterranean Fever). sUA testing practices during the 5-year follow-up period were defined as: full (≥1 test per year), moderate (≥1 test per year for 3 or 4 years), poor (≥1 test per year for 1 or 2 years) and no testing (no tests performed). Demographics, clinical characteristics, comorbidities, concurrent medications, and healthcare utilization were examined and stratified by testing practices. Chi-square tests and one-way ANOVAs were used to test for differences by testing practices. Results: We identified 15, 598 incident gout cases meeting the inclusion criteria. Mean age was 59.3±14.5 years, 79.7% were male, and 35.7% were of higher socioeconomic status. Patients' clinical history indicated that 15.2% were current smokers and 32.4% were obese. Prevalence of pre-existing comorbidities including CVD, diabetes and hypertension was 26.8%, 20.8%, and 52.5% respectively, and mean Charlson Comorbidity Index was 0.9±1.3. The distribution of annual sUA testing over the 5-year follow up in this cohort was: 5, 445 (34.9%) patients had full testing, 6, 678 (42.8%) had moderate testing, 3, 196 (20.5%) had poor testing, and 279 (1.8%) had no testing. At the end of follow-up, 25.6% of patients' last documented sUA was ≤6 mg/dL. Among patients in the groups with sUA ≤6 or ≥10 mg/dL, close to 39% had full testing, while among those with sUA between 6.1–9.9 mg/dL, full testing ranged from 31.6%–35.7%. Conclusions: Consistent with previous findings, gout patients in Clalit were on average older adults, predominately men and with concurrent comorbidities. Over three-quarters of newly diagnosed gout patients performed an annual sUA testing during at least 3 of the 5 years of follow-up. Further study is required to assess the association between regular testing and health outcomes. References: Khanna, et al. Arthritis Care Res. 2012;64(10):1431–46; Zhang et al. Ann Rheum Dis 2006;65:1213–24; Jordan et al. Rheumatology 2007;46(8):1372–4. Acknowledgement: Study funded by AstraZeneca. Disclosure of Interest: A. Benis Employee of: Clalit Health Services, D. Jaffe Employee of: Kantar Health, N. Flores Employee of: Kantar Health, H. Gabay Employee of: Clalit Health Services, R. Morlock Employee of: Ardea Biosciences, A. Klein Employee of: AstraZeneca, D. Teltsch Employee of: Evidera, J. Chapnick Employee of: Kantar Health, B. Feldman Employee of: Clalit Health Services, M. Leventer-Roberts Employee of: Clalit Health Services